POSTHARVEST QUALITY IMPROVEMENT OF NUTMEG (Myristica fragrans) - Okky Setyawati Dharmaputra; Santi Ambarwati; Ina Retnowati; Nijma Nurfadila (SEAMEO BIOTROP, 2022)
Nutmeg (Myristica fragrans) or fragrant nutmeg is an important commodity that has been used in the food and pharmaceutical industries, hence its quality should be monitored. The objectives of this study were to: 1) identify Critical Control Points (CCP) in nutmeg’s postharvest handling process and prepare nutmeg HACCP (Hazard Analysis and Critical Control Point) System and 2) provide a recommendation on GHP (Good Handling Practices) of nutmeg in order to maintain its quality in relation to food safety issue which is very important for international trade. Ripe fruits of nutmeg were collected after the fruits had reached maturity and fallen from their trees. A paranet was placed under each nutmeg tree to prevent the ripe nutmeg fruits from falling on the ground. The subsequent processes were taking out the nutmeg seeds from the fruits and separating the nutmeg seeds from the pulps and maces. After that, the nutmeg seeds underwent the drying process by using the smoke- and oven-dried methods until the moisture content of the nutmeg seeds was reduced by 10%. Subsequently, the nutmeg seeds were divided into two parts, prior to the storing process. The first part was fumigated by using phosphine (2 g/m3) for eight days and the second part was not fumigated. The sampling of nutmeg seeds was conducted at the beginning of storage and after four months of storage. The parameters observed were moisture content, percentage of damaged kernels, the population of each fungal species, and aflatoxin content. The results showed that moisture content, fungal population, aflatoxin B1, and total aflatoxin contents of nutmeg kernels having been dried by using the smoke- and oven-dried methods with and without fumigation still complied with the requirements related to food safety, although the nutmegs were stored for four months. The results of this research could also determine the Critical Control Point (CCP) in the postharvest handling process of nutmegs, i.e., 1) choosing only ripe nutmeg fruits to be harvested; 2) harvesting method by preventing the ripe nutmeg fruits from falling on the ground; 3) drying process of nutmeg seeds should be conducted immediately after separating the nutmegs from the maces by using the smoke- or oven-dried methods; and 4) nutmeg seeds were stored with the shells.